2021
DOI: 10.3389/fsurg.2021.631053
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Intraoperative Neurophysiological Monitoring During the Clipping of Unruptured Intracranial Aneurysm: Diagnostic Efficacy and Detailed Protocol

Abstract: Background: Intraoperative neurophysiological monitoring (IONM) has been widely applied in brain vascular surgeries to reduce postoperative neurologic deficit (PND). This study aimed to investigate the effect of IONM during clipping of unruptured intracranial aneurysms (UIAs).Methods: Between January 2013 and August 2020, we enrolled 193 patients with 202 UIAs in the N group (clipping without IONM) and 319 patients with 343 UIAs in the M group (clipping with IONM). Patients in the M group were intraoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Unfortunately, these conventional treatments all have many difficulties for giant intracranial aneurysms, such as huge aneurysm, thin wall, easy rupture and bleeding, wide aneurysm neck, difficult or impossible to clip. It is not suitable for tamponade, or the pituitary gland is still compressed after tamponade, and it is difficult to improve the symptoms of patients [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these conventional treatments all have many difficulties for giant intracranial aneurysms, such as huge aneurysm, thin wall, easy rupture and bleeding, wide aneurysm neck, difficult or impossible to clip. It is not suitable for tamponade, or the pituitary gland is still compressed after tamponade, and it is difficult to improve the symptoms of patients [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The EP modalities applied to IONM differ slightly in their coverage area. MEP is more sensitive to subcortical ischemia; on the other hand, SSEP is more sensitive to cortical ischemia [ 13 , 29 ]. The recipient vessel in STA-MCA bypass surgery is the M4 branch.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative neurophysiological monitoring (IONM) is widely used in open cranial surgeries, mainly as a precautionary measure to detect adverse events during surgery and to minimize the neural insult through subsequent rescue interventions [ 12 , 13 ]. Many previous studies have demonstrated its efficacy in reducing instances of postoperative neurologic deficits (PND) and in the attainment of better outcomes with open cranial surgeries [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of EP deterioration, we performed rescue interventions according to our protocol, as des-cribed in detail previously [13]. The basic principles of rescue intervention are fast evaluation and a multidisciplinary approach when an EP change meets the warning criteria [5,14,15].…”
Section: Intraoperative Neurophysiological Monitoring (Ionm) Criteria...mentioning
confidence: 99%